Identifying common metrics for evaluating school-based healthy lifestyles programs in seven countries: introduction to workshop proceedings. - Pérez-Escamilla, Rafael; Alberg-Seberich, Michael (Food and nutrition bulletin, 2014)
The worldwide childhood obesity pandemic highlights the need to instill healthy lifestyle habits in children and youths, in particular fostering and facilitating healthy eating behaviors and a high degree of physical activity. To achieve this it's important to strengthen local program evaluation capacity.
Keywords: Adolescent; Child; Child Welfare; Child, Preschool; Diet; Health Promotion; Humans; Life Style; Obesity; Program Evaluation; School Health Services; Spain